Preparation method and application of nano high-entropy single-phase perovskite oxide
By using nanocarbon nanotubes as templates and high-temperature calcination methods in the preparation of high-entropy perovskite oxides, the problems of complex processes and high-cost in the prior art were solved, and stable and uniform nano high-entropy perovskite oxidation were prepared. , used in supercapacitor electrodes, exhibits good electrochemical properties.
Patent Information
- Application Number
- CN202411190833.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-13
AI Technical Summary
The existing high-entropy perovskite oxide preparation methods have problems such as complex process, high cost, low yield and product particle agglomeration, which limits its wide application in the field of supercapacitors.
The nanoform carbon nanotubes were used as the sacrificial template, combined with the high-temperature calcination method, and by accurately weighing the metal salt in ethanol, stirring, and then drying and calcining, stable nano high-entropy single-phase perovskite oxide was prepared.
It realizes high-entropy perovskite oxides with low preparation cost, simple process, strong repeatability, and uniform nanomorphology distribution, and has good electrochemical properties and is suitable for supercapacitor electrode materials.
Smart Images

Figure CN119118666A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a preparation method and application of a nano high-entropy single-phase perovskite oxide, belonging to the technical field of capacitors. Background Art
[0002] As a new type of efficient energy storage device, supercapacitors are widely used in the field of energy storage. Among them, Faraday capacitor materials usually show higher energy storage density. At present, high power density materials such as transition metal layered hydroxides and conductive polymers that have been widely reported are widely controlled by Faraday processes. High entropy perovskite oxides have certain advantages in thermal stability, chemical stability and structural stability due to their compositional diversity and unique crystal structure. In addition, they have multi-element coordination and more diverse electronic structures. They may show more significant Faraday processes and show the potential for application in supercapacitors. In addition, nano-sized high entropy perovskites are highly favored in electrochemical reactions.
[0003] High-entropy perovskite oxides are oxides with a perovskite structure composed of five or more elements in equimolar or nearly equimolar amounts, and their configuration entropy value Sconfig≥1.61R. They are still in the initial stage of research. The main methods for preparing high-entropy ceramics include hot pressing sintering, sol-gel method, electrospinning method, solid phase method, spark plasma sintering, and spray pyrolysis. These technical methods have many problems such as complex preparation process, high cost, low yield or product particle agglomeration, which limits their wide application. Therefore, exploring new preparation methods for nano high-entropy perovskite materials is of great significance for carrying out research work in new directions. Summary of the invention
[0004] In view of this, the present application first provides a method for preparing nano high-entropy single-phase perovskite oxide, which is simple and easy to operate, low-cost, green and environmentally friendly, and highly repeatable. The prepared high-entropy perovskite has a stable structure, strong crystallinity, is distributed in nano form, and has uniform element distribution.
[0005] Specifically, the present application is implemented through the following scheme: A method for preparing nano high entropy single-phase perovskite oxide, characterized in that: The nano high entropy single-phase perovskite oxide satisfies the structural formula: La(M 0.8 X 0.2 ) O3, M includes the elements Fe, Co, Ni, Cr, X is any one of Cu, Zn, Mn, The preparation steps of the above-mentioned nano high entropy single-phase perovskite oxide are as follows: Step 1: accurately weighing the nitrate of metal lanthanum, the metal nitrate containing the M element, and the nitrate containing the X element in an ethanol solution according to the stoichiometric ratio corresponding to the nano high entropy single-phase perovskite oxide structural formula, and stirring to obtain a mixed solution; Step 2, adding nano-sized carboxylated multi-walled carbon nanotubes as sacrificial templates to the mixed solution obtained in step 1, standing overnight, and then completely drying the mixed solution to obtain a solid precursor; Step 3: Place the precursor obtained in step 2 in an alumina ark, and calcine it in a tube furnace to obtain nano high-entropy single-phase perovskite oxide.
[0006] The present invention adopts a method combining sacrificial template and high-temperature calcination, uses nano-shaped carbon nanotubes as sacrificial templates, adds them into a metal nitrate mixed solution and fully mixes them, and directly calcines them at high temperature after the solution is dried to obtain high-entropy perovskite oxide nanoparticles with good crystallinity. The preparation method has low cost, simple process, strong repeatability, high preparation yield, and is easy to promote and apply.
[0007] Further, as a preference: In step one: The nitrate of metallic lanthanum is lanthanum nitrate, and preferably lanthanum nitrate hexahydrate.
[0008] The metal nitrate containing the element M includes iron nitrate, cobalt nitrate, nickel nitrate and chromium nitrate, and is preferably iron nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, or chromium nitrate nonahydrate.
[0009] The nitrate containing the element X is any one of copper nitrate, zinc nitrate and manganese nitrate, and is preferably manganese nitrate tetrahydrate, copper nitrate trihydrate or zinc nitrate hexahydrate.
[0010] In the mixed solution, the total nitrate concentration is 0.05 ~ 0.3 mmol / ml.
[0011] During the batching process, the molar content of each component element at the B position is controlled to be 20% and the total content is 100%. The configuration entropy of the obtained material Sconfig≥1.61R, which meets the definition of high entropy materials, so that better product performance can be achieved.
[0012] In step 2: The inner diameter of the carboxylated multi-walled carbon nanotube is not less than 5 nm, and the length is not less than 10 μm.
[0013] The drying temperature is 60 ~ 90 ℃.
[0014] In step three: The calcination temperature is 600-1000°C, and the calcination time is 2-4 hours. More preferably, the temperature in the tubular furnace is increased from room temperature to the calcination temperature at a heating rate of 3-5°C / min.
[0015] The second purpose of this application is to provide the application of the nano high entropy single-phase perovskite oxide prepared by the above method as a supercapacitor electrode material Nano high entropy single-phase perovskite oxide, conductive carbon black and PVDF (polyvinylidene fluoride) were mixed in a mass ratio of 90:5:5, diluted with NMP (N-methylpyrrolidone), fully ground and mixed, and then coated on a 1×1 cm 2 A high entropy perovskite oxide electrode is obtained on a carbon cloth. The high entropy perovskite oxide electrode is used for a supercapacitor. A nano high entropy single-phase perovskite oxide is used as a working electrode, a platinum sheet is used as a counter electrode, and glass mercuric oxide is used as a reference electrode. Cyclic voltammetry test, constant current charge-discharge test, and AC impedance spectroscopy test are performed in a three-electrode system.
[0016] The present application prepares high-entropy perovskite oxide nanoparticles by a sacrificial template method combined with a high-temperature calcination method. The method is simple and easy to operate, low cost, green and environmentally friendly, and highly repeatable. The prepared high-entropy perovskite has a stable structure, strong crystallinity, and is distributed in a nano-form with uniform element distribution. The prepared high-entropy perovskite is used as a supercapacitor electrode material, exhibiting low internal resistance and high specific capacitance, and having good electrochemical properties, and is a very promising energy storage material. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0018] Figure 1 The XRD diagram of the nano high entropy single-phase perovskite oxide obtained in the example is compared with the standard card; Figure 2 The scanning electron microscope (SEM) and X-ray energy dispersive spectroscopy (EDS) analysis of nano high entropy single-phase perovskite oxide; Figure 3 The nano high entropy single-phase perovskite oxide obtained in Example 1 is 10 mV s -1 Cyclic voltammetry curves at scan rates; Figure 4 The charge and discharge curve of the nano high entropy single-phase perovskite oxide obtained in Example at a current density of 0.2A g-1; Figure 5 This is the AC impedance spectrum of the nano high-entropy single-phase perovskite oxide obtained in Example. DETAILED DESCRIPTION
[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0020] Example 1
[0021] In this embodiment, the preparation process of the nano high entropy single-phase perovskite oxide is as follows: (1) Accurately weigh 0.004 mol of lanthanum nitrate hexahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, manganese nitrate tetrahydrate, chromium nitrate nonahydrate, copper nitrate trihydrate, and zinc nitrate hexahydrate and dissolve them in 40 ml of ethanol to prepare a mixed salt solution. The molar ratio of the metal salts is 1:0.2:0.2:0.2:0.2:0.2.
[0022] (2) 0.6 g of multi-walled carboxylated carbon nanotubes was added to the salt solution. The ultrasonic power was 90 W and the ultrasonic time was 1 h. After standing for 12 h, the prepared salt solution was dried in an oven at 90 °C for 12 h.
[0023] (3) The dried solid was collected and placed in an alumina ark, which was placed in a tube furnace and heated to 700°C at 3°C / min. After being kept at 700°C for 3 h, the solid was cooled with the furnace to obtain nano high entropy single-phase perovskite oxide La(FeCoNiCr) 0.8 Mn 0.2 O3, recorded as La4M-Mn HEP.
[0024] The nano high entropy single-phase perovskite oxide La4M-Mn HEP prepared in the above steps is applied, and the process is as follows: 0.36 g La4M-Mn HEP, 0.02 g PVDF, and 0.02 g conductive carbon black were added in sequence, ground, diluted with 2 ml NMP, stirred thoroughly, and coated on a 1×1 cm 2 The electrode is obtained by means of carbon cloth.
[0025] Example 2
[0026] The configuration of this embodiment is the same as that of embodiment 1, except that in step (1), copper nitrate trihydrate is used instead of manganese nitrate tetrahydrate to obtain nano high entropy single-phase perovskite oxide La(FeCoNiCr) 0.8 Cu 0.2 O3, recorded as La4M-Cu HEP.
[0027] Example 3
[0028] The configuration of this embodiment is the same as that of embodiment 1, except that in step (1), zinc nitrate hexahydrate is used instead of manganese nitrate tetrahydrate to obtain a nano high entropy single-phase perovskite oxide La(FeCoNiCr) 0.8 Zn 0.2 O3, recorded as La4M- Zn HEP.
[0029] The performance of the above products was evaluated: 1) Crystallinity: The La4M-Mn HEP, La4M-Cu HEP and La4M-Zn HEP perovskite materials prepared in Examples 1 to 3 were subjected to X-ray diffraction, and the obtained diffraction patterns were as follows: Figure 1 As shown. Figure 1 It was found that the materials obtained in Examples 1-3 were all single-phase, with a stable orthorhombic structure, consistent with the PDF#71-1231 card (i.e., #71-1231 LaCrO3Pbnm), and had good crystallization performance. This indicates that the preparation method obtained a stable single-phase high-entropy perovskite with good crystallization performance.
[0030] 2) Surface morphology: Scanning electron microscope images of La4M-Mn HEP, La4M-Cu HEP and La4M-Zn HEP nano high entropy single-phase perovskite materials prepared in Example 1, Example 2 and Example 3 are shown in Figure 2 From (a), (b), and (c) in the figure, it can be seen that irregularly scattered nano-sized particles can be seen on the surfaces of La4M-Mn HEP, La4M-Cu HEP, and La4M-Zn HEP materials, that is, the surface morphology of the perovskite materials prepared by the above method is irregularly scattered nano-sized particles. Taking Example 2 as an example, X-ray energy spectrum (EDS) was performed, and the results are as follows: Figure 2 As shown in (d) to (i), La, Co, Cr, Fe, Ni, and Cu are uniformly distributed, indicating that the perovskite obtained by the preparation method has a nano-morphology, which is conducive to increasing the specific surface area and electrochemical activity of the material. The applicant also conducted X-ray energy spectrum verification on Examples 1 and 3, and the results were consistent.
[0031] 3) Electrochemical performance test: The electrodes prepared from the La4M-Mn HEP, La4M-Cu HEP and La4M-ZnHEP perovskite materials prepared in Examples 1 to 3 were used as working electrodes, platinum sheets were used as counter electrodes, and glass mercuric oxide was used as reference electrodes. Cyclic voltammetry test, constant current charge and discharge test, and AC impedance spectroscopy test were performed under a three-electrode system.
[0032] (1) Cyclic voltammetry test: Figure 3 As shown in the figure, it can be seen that the electrodes prepared from the La4M-Mn HEP, La4M-Cu HEP, and La4M-Zn HEP perovskite materials provided in Examples 1 to 3 have a voltage window of -0.5 to 0 V, 10 mV s -1 At a scan rate of , the La4M-Cu HEP electrode prepared in Example 2 has the largest redox current and the highest specific capacitance.
[0033] (2) Constant current charge and discharge test: Figure 4 As shown in Figure 2, the La4M-Mn HEP, La4M-Cu HEP, and La4M-Zn HEP electrodes prepared in Examples 1 to 3 have a current density of 0.2 A g in the voltage window of -0.5 to 0 V. -1 The specific capacities are 48.0 F g -1 , 177.0 F g -1 , 70.8 F g -1 . La4M-Cu HEP has the highest specific capacitance.
[0034] (3) AC impedance spectroscopy test: The electrodes prepared from the La4M-Mn HEP, La4M-Cu HEP, and La4M-ZnHEP perovskite materials provided in Examples 1 to 3 were subjected to AC impedance spectroscopy test. Figure 5 As shown, the results show that the internal resistance of La4M-Mn HEP, La4M-Cu HEP, and La4M-Zn HEP electrodes are 1.28 Ω, 0.24 Ω, and 0.37 Ω, respectively, and the diffusion resistance is 2.04 Ω, 0.84 Ω, and 2.36 Ω, respectively. La4M-Cu HEP has the smallest impedance value.
[0035] In summary, the nano high-entropy single-phase perovskite oxide material prepared by the method of the present application has a stable structure and good electrochemical properties, among which the La4M-Cu HEP material has the highest specific capacitance and exhibits good electrochemical properties. It is used for electrode preparation and for capacitors, and its performance shows that the perovskite material has good application prospects.
[0036] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. A method for preparing nano high entropy single-phase perovskite oxide, Features: The nano high entropy single-phase perovskite oxide satisfies the structural formula: La(M 0.8 X 0.2 ) 3 In the formula, M includes the elements Fe, Co, Ni, and Cr, and X is any one of Cu, Zn, and Mn. The preparation steps of the above-mentioned nano high entropy single-phase perovskite oxide are as follows: Step 1: accurately weighing the nitrate of metal lanthanum, the metal nitrate containing the M element, and the nitrate containing the X element in an ethanol solution according to the stoichiometric ratio corresponding to the nano high entropy single-phase perovskite oxide structural formula, and stirring to obtain a mixed solution; Step 2, adding nano-sized carboxylated multi-walled carbon nanotubes as sacrificial templates to the mixed solution obtained in step 1, standing overnight, and then completely drying the mixed solution to obtain a solid precursor; Step 3: Place the precursor obtained in step 2 in an alumina ark, and calcine it in a tube furnace to obtain nano high-entropy single-phase perovskite oxide.
2. A method for preparing a nano high entropy single-phase perovskite oxide according to claim 1, Features: In step 1, the nitrate of metal lanthanum is lanthanum nitrate; the metal nitrate containing element M includes iron nitrate, cobalt nitrate, nickel nitrate and chromium nitrate; the nitrate containing element X is any one of copper nitrate, zinc nitrate and manganese nitrate.
3. The method for preparing a nano high entropy single-phase perovskite oxide according to claim 1, Features: In step 1, the total concentration of nitrate in the mixed solution is 0.05 ~ 0.3 mmol / ml.
4. The method for preparing a nano high entropy single-phase perovskite oxide according to claim 1, Features: In step 2, the inner diameter of the carboxylated multi-walled carbon nanotube is not less than 5 nm, and the length is not less than 10 μm.
5. The method for preparing a nano high entropy single-phase perovskite oxide according to claim 1, Features: In step 2, the drying temperature is 60 ~ 90 °C.
6. The method for preparing a nano high entropy single-phase perovskite oxide according to claim 1, Features: In step three, the calcination temperature is 600 ~ 1000 ° C, and the calcination time is 2 ~ 4 h.
7. The method for preparing a nano high entropy single-phase perovskite oxide according to claim 6, Features: In step 3, the temperature in the tubular furnace is increased from room temperature to calcination temperature at a heating rate of 3 to 5 °C / min.
8. The method for preparing a nano high entropy single-phase perovskite oxide according to claim 1, Features: In step 1, lanthanum nitrate hexahydrate, iron nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate, manganese nitrate tetrahydrate / copper nitrate trihydrate / zinc nitrate hexahydrate are weighed respectively according to a nitrate molar ratio of 1:0.2:0.2:0.2:0.2; In step 2, after adding nano-sized carboxylated multi-walled carbon nanotubes to the mixed solution, the solution was ultrasonically treated at 90 W for 1 h, allowed to stand for 12 h, and then dried in an oven at 90 °C for 12 h; In step three, the temperature in the tube furnace is raised to 700 °C at 3 °C / min, and after being kept at 700 °C for 3 h, the furnace is cooled to obtain nano high-entropy single-phase perovskite oxide.
9. A use of the nano high entropy single-phase perovskite oxide according to any one of claims 1 to 8, Features: Nano high entropy single-phase perovskite oxide, conductive carbon black and PVDF were mixed in a mass ratio of 90:5:5, diluted with NMP, fully ground and mixed, and then coated on a 1×1 cm 2 On carbon cloth, a high entropy perovskite oxide electrode was obtained.
10. Use of a nano high entropy single-phase perovskite oxide according to claim 9, Features: The high entropy perovskite oxide electrode is used as a working electrode for a supercapacitor.
Citation Information
Patent Citations
Novel B-site five-membered high-entropy perovskite type oxide material and preparation method thereof
CN110467227A
Novel perovskite type high-entropy oxide material with six-membered high-entropy B site, and preparation method thereof
CN110563462A
Preparation method of high-entropy oxide ceramic fiber material
CN113754432A
Hollow spherical high-entropy oxide with microporous surface as well as preparation method and application of hollow spherical high-entropy oxide
CN114275829A
Perovskite type high-entropy oxide and preparation method and application thereof
CN115837275A
Cited By
Lanthanum-based perovskite oxide electrode material for electrochemical energy storage applications
US12534386B1
